Chemopreventive efficacy of stampidine in a murine breast cancer model - Şahin, Kazım; Orhan, Cemal; Ozercan, Ibrahim Hanifi; Tuzcu, Mehmet; Elibol, Birsen; Sahin, Taha Koray; Uckun, Fatih Mehmet (Taylor & Francis Ltd, 2020)
Background: The purpose of the present study was to examine the chemopreventive effect of stampidine, an aryl phosphate derivative of stavudine, in side by side comparison with the standard anti-breast cancer drug paclitaxel in the well-established 7,12-dimethylbenz(a)anthracene (DMBA)-induced murine breast cancer model. Methods: Groups of 20 female mice were challenged with the DMBA. DMBA-challenged mice were assigned to various chemoprevention treatments, including stampidine, paclitaxel, and stampidine plus paclitaxel according to the same treatment schedules for 25 weeks. Results: Stampidine resulted in substantially reduced numbers of tumors, tumor weight as well as tumor size in DMBA-treated mice. Stampidine was as effective as paclitaxel in the model and their combination exhibited greater chemopreventive activity, as measured by reduced tumor incidence and improved tumor-free survival as well as overall survival of DMBA-treated mice. The length of time for the initial tumor to appear in DMBA-challenged mice treated with stampidine was longer than that of mice treated DMBA-challenged control mice. Tumors from mice treated with stampidine or stampidine plus paclitaxel displayed unique changes of a signature protein cassette comprised BRCA1, p21, Bax, and Bcl-2. Conclusion: Stampidine has potent chemopreventive activity and is as effective as the standard chemotherapy drug paclitaxel in the chemical carcinogenesis.
Keywords: Stampidine; paclitaxel; apoptosis; breast cancer; mice